ANALISIS BUDAYA ORGANISASI PADA INSTITUSI PEMERINTAHAN X MENGGUNAKAN OCAI (ORGANIZATIONAL CULTURE ASSESSMENT INSTRUMENT) - Ratna Jupitawati; Anissa Lestari Kadiyono (BBM (Buletin Bisnis & Manajemen), 2021)
This study aims to analyze organizational culture at government institution X using OCAI(Organizational Culture Assessment Instrument). The research population is all employees ofGovernment Institution X consisting of groups of rank IV, III and II. Based on the results obtained,the appreciation of the employees who devote themselves to Government Institution X theyappreciate the organization of Government Institution X as an organization with a Hierarchy type.This reflects the existence of a control system management to ensure that procedures,measurement, and monitoring systems are in place to keep processes and performance undercontrol. Focus on coordination, fostering coordination within the organization as well as withexternal work units to obtain accurate cross-border information to carry out its activities. Similarly,expectations for changes in organizational culture in the future, they do not expect changes inorganizational culture, this is felt in the three groups of ranks.Keywords: organizational culture, goverment institution, ocai.